Trends and in-hospital mortality of Acute Coronary Syndrome at Shahid Gangalal National Heart Centre, Kathmandu, Nepal during 2001-2012 - Adhikari, Chandra Mani; Sharma, Deewakar; Malla, Rabi; Rajbhandari, Sujeeb; Raut, Roshan; Baidya, Sajan; Dhungana, Murari; Prajapati, Dipanker; KC, Man Bahadur (Journal of Advances in Internal Medicine, 2014)
Background and aims: Acute coronary syndrome (ACS), which comprises acute ST-segment elevation myocardial infarction, non-ST segment elevation myocardial infarction and unstable angina is a major health problem and represents a large number of hospitalizations annually worldwide. We aim to describe pattern of the ACS admission and in-hospital mortality at tertiary national heart centre of the country. Methods: A hospital database was used to analyze all 7424 patients admitted in coronary care unit of the centre for ACS from September 2001 till December 2012. We evaluated trend of ACS admission and in-hospital mortality. Results: Five thousand three hundred ninety one (72.6%) were male and two thousand thirty three (27.4%) were female. Patient of 21years to 98 years were admitted for ACS .Four thousand five hundred and ninety nine(61.9%) patient were admitted due to ST elevation myocardial infarction, whereas one thousand nine hundred and thirteen (25.8%) were admitted for Unstable angina and nine hundred twelve (12.3%) were admitted for Non ST elevation myocardial infarction. In-hospital mortality was 5.74% for acute coronary syndrome. There was significant difference in in-hospital mortality between ST elevation myocardial infarction (7.76%), Non ST segment elevation acute coronary syndrome (3.61%) and Unstable Angina (1.88%).There is a gradual increase in Primary Percutaneous Coronary intervention as a mode of reperfusion therapy whereas there is a decrease in the rate of thrombolysis. Conclusion: Our study provides us some important information about the trend and in-hospital mortality rate in national heart centre. Though it is a single centre study can provide us the insight of the ACS outcome. DOI: http://dx.doi.org/10.3126/jaim.v3i1.10698 Journal of Advances in Internal Medicine 2014;03(01):23-26